2021
DOI: 10.33824/pjpr.2021.36.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Psychological Well-being, and Emotional Regulation: A Comparative Study of Military Personnel Vs. Civilian Population

Abstract: Present research aimed to know the difference between military personnel with endurance training and civilian population (with no endurance training), with respect to resilience, psychological well-being, and emotional regulation. Correlation and comparative design was used for this study. A sample of 180 participants with age range of 20-55 years was taken from different walks of military units and civilian population by using snowball sampling, and purposive sampling strategies respectively. The Adult Resili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In general, this outcome validated the idea that students who were able to realize themselves along with their true potentials, openness to experience, and adequate relationships with others can adapt well in their environment during the adverse situation. The findings of the present research are consistent with the local and international research evidences (Bano & Pervaiz, 2020;Dasti et al, 2018;Färber & Rosendahl, 2018;Poole, Dobson, & Pusch, 2017;Sohail & 2021) that support the correlation between psychological Well-being and resilience and association of increased resilience with decreased frequency of psychological disorders. According to a recent research (Sohail & Ahmed, 2021) optimal level of resiliency is significant predictor of psychological well-being among young population.…”
Section: Discussionsupporting
confidence: 92%
“…In general, this outcome validated the idea that students who were able to realize themselves along with their true potentials, openness to experience, and adequate relationships with others can adapt well in their environment during the adverse situation. The findings of the present research are consistent with the local and international research evidences (Bano & Pervaiz, 2020;Dasti et al, 2018;Färber & Rosendahl, 2018;Poole, Dobson, & Pusch, 2017;Sohail & 2021) that support the correlation between psychological Well-being and resilience and association of increased resilience with decreased frequency of psychological disorders. According to a recent research (Sohail & Ahmed, 2021) optimal level of resiliency is significant predictor of psychological well-being among young population.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, there have been limited studies that have examined whether there are differences in resilience between military and civilian individuals. The few studies that have compared the two groups have found inconsistent results (e.g., support: Sanborn et al., 2021—US psychological operations Army brigade to community college students; no support: Sohail & Ahmad, 2021—convenient samples of military personnel and civilians in Pakistan). There are some compelling reasons why military personnel might be more resilient such as personnel selection, military culture, unit cohesion, sense of control and agency during high stress events, and access to resilience training in the military (Jex et al., 2013).…”
Section: Introductionmentioning
confidence: 99%